Effect of Storage of Fruit on Quality of Citrus Peel Essential Oil - Jalgaonkar, Kirti R; Jha, S K; PAL, R K; Sethi, S; Raina, Archana P; Dubey, A K (Journal of Agricultural Engineering, 2013)
Physical and chemical quality of essential oil extracted from peel of four stored citrus species (Jatti khatti, Sohsarkar, grapefruit and pummelo) were determined. Refractive indices of peel oil from Jatti khatti, Soh sarkar,grapefruit and pummelo were 1.467, 1.469, 1.471 and 1.471, respectively. Essential oils obtained from all thespecies were soluble in 95% alcohol at different levels (3-4 ml). While acid value decreased, ester and saponificationvalues of essential oil increased with increasing physiological loss in mass when extracted from fruits stored forincreasing duration at both ambient as well as refrigerated conditions. The essential oil from grapefruit had leastacid value, while its ester and saponification values were highest indicating its better quality. Quantitatively, themost representative monoterpene was observed to be limonene with concentration of 95.13, 96.23, 93.57, 96.41%in oils of Jatti khatti, Soh sarkar, grapefruit, and pummelo, respectively.